Highly stable graphene-assisted tunable dual-wavelength erbium-doped fiber laser - Ahmad, Harith; Abdul Latif, Amirah; Abdul Khudus, Muhammad Imran Mustafa; Zulkifli, Ahmad Zarif; Zulkifli, Mohd Zamani; Thambiratnam, Kavintheran; Harun, Sulaiman Wadi (Optical Society of America, 2013)
A highly stable tunable dual-wavelength fiber laser (TDWFL) using graphene as a means to generate a highly stable output is proposed and generated. The TDWFL comprises a 1 m long, highly doped erbiumdoped fiber (EDF) acting as the linear gain medium, with a 24-channel arrayed waveguide grating acting as a wavelength slicer as well as a tuning mechanism to generate different wavelength pairs. The tuned wavelength pairs can range from 0.8 to 18.2 nm. A few layers of graphene are incorporated into the laser cavity to induce the four-wave-mixing effect, which stabilizes the dual-wavelength output by suppressing the mode competition that arises as a result of homogenous broadening in the EDF. © 2013 Optical Society of America